Endocrine and enzymatic shifts during insect diapause: a review of regulatory mechanisms - Izadi, Hamzeh (Frontiers in Physiology, 2025)
Insect diapause is a vital survival strategy that enables insects to enter a state of suspended development, allowing them to withstand unfavorable environmental conditions. During diapause, insects significantly lower their metabolic rate and build up energy reserves, which they gradually utilize throughout this period. The regulation of diapause involves a complex interaction of hormones and enzymes. Juvenile hormones (JHs) affect adults and larvae differently; in adults, the absence of JH typically triggers diapause, while in larvae, the presence of JH encourages this state. Ecdysteroids, which regulate molting and metamorphosis, are carefully controlled to prevent premature development. Reduced signaling of insulin-like peptides enhances stress resistance and promotes energy storage. Several enzymes play crucial roles in the metabolic adjustments necessary for diapause. These adjustments include the degradation of JH, the ecdysteroidogenic pathway, and the metabolism of fatty acids, glycogen, cryoprotectants, and stress responses. Understanding diapause’s molecular and biochemical mechanisms is essential for fundamental entomological research and practical applications. Despite recent advances, many aspects of diapause regulation, especially the interactions among hormonal pathways and the role of enzymes, remain poorly understood. This review analyzes approximately 250 papers to consolidate current knowledge on the enzymatic and hormonal regulation of diapause. It offers a comprehensive overview of key processes based on recent studies and suggests future research directions to fill gaps in our understanding of this significant biological phenomenon. The review also lays the groundwork for enhancing pest control strategies and ecological conservation by deepening our understanding of diapause mechanisms.